Calcium-myristoyl protein switch. - Zozulya, S (1992)
Recoverin, a recently discovered member of the EF-hand superfamily of Ca(2+)-binding proteins, serves as a Ca2+ sensor in vision. The amino terminus of the protein from retinal rod cells contains a covalently attached myristoyl or related N-acyl group. We report here studies of unmyristoylated and myristoylated recombinant recoverin designed to delineate the biological role of this hydrophobic unit. Ca2+ induces the binding of both the unmyristoylated and myristoylated proteins to phenyl-agarose, a hydrophobic support. Binding was half-maximal at 1.1 and 1.0 microM Ca2+, respectively. The Hill coefficients of 1.8 and 1.7, respectively, indicate that binding was cooperative. In contrast, Ca2+ induced the binding of myristoylated but not of unmyristoylated recoverin to rod outer segment membranes. Binding to these membranes was half-maximal at 2.1 microM Ca2+, and the Hill coefficient was 2.4. Likewise, myristoylated but not unmyristoylated recoverin exhibited Ca(2+)-induced binding to phosphatidylcholine vesicles. These findings suggest that the binding of Ca2+ to recoverin has two effects: (i) hydrophobic surfaces are exposed, allowing the protein to interact with complementary nonpolar sites, such as the aromatic rings of phenyl-agarose; and (ii) the myristoyl group is extruded, enabling recoverin to insert into a lipid bilayer membrane. The myristoyl group is likely to be an active participant in Ca2+ signaling by recoverin and related EF-hand proteins such as visinin and neurocalcin.